PENGARUH JUMLAH PENDUDUK, PENDIDIKAN, KESEHATAN DAN PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI PULAU SUMATRA - Nurul Madinah Lubis; Novya Zulva Riani (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to examine the factors influencing poverty levels on the island of Sumatra. The data used is panel data, comprising data from 10 provinces in Sumatra from 2010 to 2024. Processed data was obtained through from the Indonesian Central Statistics Agency (BPS). The research method is quantitative with a descriptive and associative approach. Panel data regression analysis was used, with the Random Effects Model (REM) being the best model. The results found that population size has a positive and significant effect on poverty levels on the island of Sumatra. Education has a negative and significant effect on poverty levels on the island of Sumatra. Health has a negative and significant effect on poverty levels on the island of Sumatra. Unemployment has a positive and significant effect on poverty levels on the island of Sumatra.